Models For Implementing Punishment Against Jarimah Khalwat Perpetrators In Aceh Province - Nur, Muhammad; Harun, Harun; Nasir, Muhammad; Dona SKD, Khairil (Faculty of Law, Universitas Brawijaya, 2024)
Jarimah khalwat is an act prohibited by Aceh Qanun Number 6 of 2014 concerning Jinayat Law. According to Jinayat Law, jarimah khalwat is resolved through criminal punishment, one of which is carried out by caning. The offense is resolved through the special criminal justice system in Aceh Province and the customs that apply in Aceh. The research aims to explore punishment models for perpetrators of Jarimah Khalwat in Aceh Province. The location was conducted in Aceh Province, specifically in Aceh Tamiang Regency, Lhokseumawe City, Pidie Regency, and Banda Aceh City. Primary data were collected through observations and interviews. Interviews were conducted with respondents using prepared interview guidelines. Secondary data were collected by studying the literature, laws and regulations, theories, and opinions of scholars. Data analysis employed qualitative methods. The study shows that the punishment for perpetrators of jarimah khalwat in Aceh Province are carried out using two models. Firstly, punishment are imposed based on customary law, namely by warning or advice. A marriage punishment and fine for violating the customs are imposed if the offense is repeated. The second punishment model is based on the Jinayat Law.